Art therapy with children on the autistic spectrum : beyond words - Evans, Kathy, 1948- (Arts Therapies., 2001)
Recent research has shown that art therapy can be particularly effective for children with autism and related communication disorders. The extensive range of symptoms experienced by autistic people makes them extremely individual in presentation, so any treatment used must be tailored to a range of varying needs. Art Therapy with Children on the Autistic Spectrum presents a new model of practice, which primarily focuses on communication difficulties. The authors describe how negative behaviours and subsequent tension may be alleviated when the autistic child is involved in interactive art making with the therapist. The book is divided into three parts: the first part explores art making processes and art work, with an emphasis on how art can be specifically communicative. A history of autism is presented within the therapeutic context. The second part challenges existing methods of practice within art therapy and considers the most appropriate approaches to treating autistic children. The last part discusses research that lead to the formulation of this specific model - methodology and assessment interventions are analysed, as well as the ongoing development of appropriate assessment instruments. Case studies of art therapy with individual autistic children demonstrate the use of the model and the outcomes. Throughout the book, it is emphasised how art therapy works as an integral part of overall management and treatment approaches to autism. It will be of particular interest to all those professionals working with autistic children and specialists in other communication disorders.